Analysis of Performance Management Based on the Baron Armstrong Model at UPTD Protection of Women and Children of Tanjungpinang City - Alif Surya Akbar; Denanto; Dinda Dwi Nabilla; Marsha Aryani; Satriadi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Performance management is a strategy to improve individual and team performance through a structured evaluation process. This study aims to analyze the application of the Baron and Armstrong performance management model at the Regional Technical Implementation Unit (UPTD) for the Protection of Women and Children (PPA) in Tanjungpinang, Riau Islands. Baron and Armstrong's model includes a cycle of vision and mission, goal setting, planning, development, and feedback. Using a descriptive qualitative approach, data were obtained through interviews, documentation and observation, using purposive sampling techniques to select relevant resource persons. Data analysis was done thematically through the stages of reduction, presentation, and conclusion drawing. The results showed that the implementation of this model has strengths in building a systematic workflow, but also faces challenges related to limited resources. This research provides recommendations for additional programs that can improve the effectiveness of women and child protection services. The findings contribute to the development of performance management strategies in similar institutions.